2021
DOI: 10.1111/tid.13759
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody treatment for COVID‐19 in solid organ transplant recipients

Abstract: Solid organ transplant (SOT) recipients are at high risk for severe coronavirus disease 2019 (COVID‐19). Studies suggest that early intervention with monoclonal antibody (MAB) treatment directed against the SARS‐CoV‐2 spike protein may reduce the risk of emergency department visits or hospitalization for COVID‐19, especially in high‐risk patients. Herein we describe our single‐center experience of 93 SOT (50 kidney, 17 liver, 11 lung, 9 heart and 6 dual‐organ) recipients with mild to moderate COVID‐19 who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 20 publications
5
44
1
1
Order By: Relevance
“…These results are in line with previous observations. 13 , 14 , 15 , 16 , 17 Moreover, the 30-day hospitalization rate after monoclonal antibody infusion in our cohort seems lower than those reported in two recent case-series (8.7% and 15%, respectively 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These results are in line with previous observations. 13 , 14 , 15 , 16 , 17 Moreover, the 30-day hospitalization rate after monoclonal antibody infusion in our cohort seems lower than those reported in two recent case-series (8.7% and 15%, respectively 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 74%
“…After adjustment for age, 30-day hospitalization rate was not statistically different between both groups (Odds Ratio 0.49, p=0.16). 24 Klein et al reported on 95 kidney transplant recipients (including 20 who received monoclonal antibody therapy) with COVID-19 between March 1,2020 and April 30, 2021. After adjustment for potential confounders, monoclonal antibody administration was associated with significant decrease in hospitalization rates (adjusted hazard ratio 0.216, p=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…High-dose corticosteroids, remdesivir, and monoclonal antibodies were the most commonly discussed treatment choices in LuTx recipients [ 3 , 9 , 73 , 94 ]. Calcineurin inhibitors were shown to block the SARS-CoV-2 replication, and together with MPA, are proposed as a possible treatment strategy for COVID-19 [ 57 , 62 , 63 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarrell et al evaluated the efficacy and safety of monoclonal antibody (mAbs) therapy in SOT recipients [ 94 ]. The mAbs therapy was safe and associated with a lower risk of hospitalization [ 94 ].…”
Section: Sars-cov-2-infected Recipient—covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation